Velocity structure beneath the southern Puna plateau: Evidence for delamination. (2nd October 2013) - Calixto, Frank J.; Sandvol, Eric; Kay, Suzanne; Mulcahy, Patrick; Heit, Benjamin; Yuan, Xiaohui; Coira, Beatriz; Comte, Diana; Alvarado, Patricia
Abstract : [1] The high elevation of the southern Puna plateau, the widespread melting of its crust, the gap in intermediate depth seismicity and the recent eruptions of ignimbrite complexes can be explained by delamination of the lithospheric mantle beneath it. To test this hypothesis, an array consisting of 73 broad band and short period seismic stations was deployed in the region for a period of 2 years starting in 2007. We inverted the data using the two plane wave approach and obtained 1‐D and 3‐D Rayleigh wave phase velocities. Our dispersion curve shows that at short periods (<70 s) the phase velocities are slightly higher than those of the Tibetan plateau and lower than those of the Anatolian plateau. At periods of 100–140 s we observe a low velocity zone that might be remnant hot asthenosphere below a flat slab (7–10 Ma). We estimate the average continental lithosphere thickness for the region to be between 100 and 130 km. Our three‐dimensional Rayleigh wave phase velocities show a high velocity anomaly at low frequencies (0.007, 0.008, and 0.009 Hz) slightly to the north of Cerro Galan. This would be consistent with the hypothesis of delamination in which a piece of lithosphere has detached and caused upwelling of hot asthenosphere, which in turn caused widespread alkaline‐collision related volcanism. This interpretation is also corroborated by our shear wave velocity model, where a high velocity anomaly beneath the northern edge of Cerro Galan at 130 km depth is interpreted as the delaminated block on top of the subducting Nazca slab. Key Points: A 3D velocity structure is provided for the Southern Puna Plateau We imaged a delaminated block beneath the Puna plateau Ignimbrite flare up in Cerro Galan Region may not be over